Tilt based passive optimizations for microfluidics and lab-on-chip devices - A simulation study - Jeroish, Z. E.; Bhuvaneshwari, K. S.; Narayanamurthy, Vigneswaran; Premkumar, R.; Fahmi, Samsuri (School of Engineering, Taylor’s University, 2020)
Microfluidics-based biochip applications have been increased abruptly in multiple fields because of the advantages in manifolds, which include decreased test sample utilization and reagent consumption with numerous purposes and highly listed benefits. In general, microfluidics involves two different techniques, namely active and passive methods, to enable the fluid flow within the channel that is mounted on the biochip. In this study, we focus on hydrostatic pressure-driven passive pumping methodology as it does not require any external actuators or power source to assist the flow. This technique solely depends on the gravitational pull to enhance fluid flow within the channel. The ultimate aim of this study is to design a microfluidic channel in which the geometrical parameters are optimized, and the respective velocity profile is obtained. The geometrical parameters such as the angle of contact between the channel and the ground (θ), channel dimension, and reservoir dimensions which decide the performance of the microfluidic device. These optimizations in the channels are performed as a theoretical simulation study in 3D modeling software COMSOL Multiphysics 5.0 to analyze the fluid velocity, where θ is varied between 0 degrees and 70 degrees and the channel width (wc) and channel height (hc) are varied between 1 mm to 10 mm and 0.05 mm to 0.5 mm, respectively. Also, the reservoir diameter (dr) and reservoir height (hr) are varied between 6 mm and 10 mm, and 0.5 mm and 3 mm, respectively for analyzing the velocity profiles. From the obtained results, it is observed that the overall flow velocity ranges between 7.27×10-5 – 3.77870×10-2 m/s. Hence an individual can select the best optimizations of the geometrical parameters and their respective velocity for designing a microfluidic chip with specific applications upon following this article.